1994
DOI: 10.1128/iai.62.10.4374-4379.1994
|View full text |Cite
|
Sign up to set email alerts
|

Increased concentrations of interleukin-6 and interleukin-1 receptor antagonist and decreased concentrations of beta-2-glycoprotein I in Gambian children with cerebral malaria

Abstract: To investigate the pathogenic versus the protective role of cytokines and toxin-binding factors in Plasmodium falciparum infections, we measured the concentrations of tumor necrosis factor alpha, interleukin-la (IL-la), IL-1,, IL-1 receptor antagonist, and IL-6, as well as soluble receptors of tumor necrosis factor and IL-6 (sIL-6R) in serum of Gambian children with cerebral malaria, mild or asymptomatic malaria, or other illnesses unrelated to malaria. Because cytokine secretion may be triggered by toxic stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…Several cell types produce IL-10 and IL-1Ra, but monocytes are likely to be one of the main sources. Increased concentrations of IL-10 have previously been detected in children with malaria [11], in particular in children with severe malaria, and we have found that the concentrations of IL-1Ra were associated with disease severity in Gambian children with malaria [7].…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Several cell types produce IL-10 and IL-1Ra, but monocytes are likely to be one of the main sources. Increased concentrations of IL-10 have previously been detected in children with malaria [11], in particular in children with severe malaria, and we have found that the concentrations of IL-1Ra were associated with disease severity in Gambian children with malaria [7].…”
Section: Discussionsupporting
confidence: 60%
“…The serum protein 2 -GPI binds to negatively charged phospholipids and may therefore bind to the malaria parasite toxin. Although binding of 2 -GPI to this toxin has not been reported, we have previously shown that concentrations of 2 -GPI are significantly decreased in children dying of cerebral malaria [7]. In this study, we found that children with asymptomatic P. falciparum infections had higher concentrations of 2 -GPI compared with children with malaria.…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations